Moving Opportunism to the Back Seat: Bounded Rationality, Costly Conflict, and Hierarchical Forms - Foss, Nicolai J.; Weber, Libby (Academy of Management Review, 2016)
We augment transaction cost economics’ bounded rationality assumption with heuristics (framing) and cognitive biases to expand the understanding of hierarchical governance in the theory. In transaction cost economics opportunism traditionally takes the front seat, while bounded rationality is primarily relegated to the support role of invoking incomplete contracts. The theory also suggests that hierarchical governance effectively mitigates opportunism-based transaction costs, making it difficult to explain why hierarchies are not always used. However, when an augmented bounded rationality assumption is incorporated into transaction cost economics, we argue, first, that bounded rationality is a separate source of transaction costs and, second, that these costs are not equally mitigated by all forms of hierarchy. Instead, different hierarchical forms are associated with particular frames and social referents that naturally enhance specific bounded rationality–based conflicts, allowing certain hierarchical forms to mitigate bounded rationality–based transaction costs better than others. As a result, bounded rationality takes a front seat in the theory, addressing prior critiques of the theory, expanding the governance questions addressed by the theory, and creating a new moderating role for asset specificity in internal exchanges.